Effect from the vitamin D serum and supplement in patients infection for the COVID-19 - Mejía-Zambrano, Henry (2022)
Background: The COVID-19 disease caused by the novel severe acute respiratory syndrome coronavirus 2, which appeared in late 2019 in Hubei province, Wuhan region of the People's Republic of China. Objective: To determine the effects of serum vitamin D and supplement in patients infected with COVID-19. Methods: Experimental and observational studies were included in this systemic review; studies on the effects of serum vitamin D and supplement in patients with COVID-19; studies with available text and studies in the English and Spanish language were included. A formal narrative synthesis of the collected data was carried out, no formal statistical synthesis was carried out. The methodological quality of the articles was evaluated using the quality assessment tools of the National Heart, Lung and Blood Institute (NHLBI). Results: Seropositivity in patients with SARS-CoV-2 was not associated with vitamin D3 deficiency (OR=0.99; 95% CI=0.85-1.16). The difference between the vitamin D3 group and the placebo group was not significant for hospital mortality (7.6% versus 5.1%; [95% CI= -4.1% to 9.2%]. Admission to the intensive care unit (16.0% vs 21.2%; [95% CI= -15.1% to 4.7%]; respectively. Conclusion: Vitamin D deficiency causes increased hospitalization and severity in patients infected with COVID-19. In addition, vitamin D administration does not appear to produce beneficial or adverse events. More randomised clinical trials are needed.